TEACHER'S QUESTIONING STRATEGIES AND STUDENTS' RESPONSES IN YOUNG LEARNERS' CLASSROOM INTERACTION - Haliani, Hani (2013)
This study aimed to investigate: (1) the teacher's questioning strategies that were used by a teacher in young learners' classroom interaction, (2) the effect of the teacher's questioning strategies towards students 'responses. This study was conducted qualitatively by using case study method. An English teacher and 15 students were involved in this study. The transcripts from the observations were analyzed to reveal the teacher's questioning applied in the classroom based on the framework from Chaudron and Wu. The interview was also conducted to enrich the data. The findings of the study revealed that there were five teacher's questioning strategies that were used by the teacher in the classroom observation. They were repetition, simplification, blank-filling, code-switching, and wait-time. Four of them were mentioned by the teacher in the interview. They were repetition, simplification, wait-time and code-switching. Regarding students' responses, two types of students' responses were discovered in this study, they were relevant response 84 %, irrelevant and response 16%. From the percentage, it could be seen that the number of students' relevant responses was higher than the number of irrelevant responses. Keywords: questioning strategies, students' responses, young learners' classroom interaction